Antibiotic Resistance Patterns in Clinical Bacterial Isolates from Gharyan City, Libya - Hiyam Younis Aballu (AlQalam Journal of Medical and Applied Sciences, 2026)
Antimicrobial agents are widely used to treat bacterial infections; however, their misuse contributes to the growing problem of antibiotic resistance. This study assessed the prevalence of antibiotic resistance among bacterial isolates from patients in Gharyan City, Libya, and explored behavioral factors influencing resistance. Between January and June 2024, 66 clinical samples (urine, stool, vaginal swabs, blood, pus, and sputum) were collected from seven medical laboratories. A questionnaire survey was conducted among three groups: medical workers (n=50), non-medical individuals (n=50), and pharmacists (n=50). Laboratory identification employed selective media, Gram staining, and microscopy, while antibiotic susceptibility was tested using disc diffusion. Results revealed widespread inappropriate antibiotic use: 70% of pharmacists dispensed antibiotics without prescriptions, 40% provided incorrect dosages, and only 10% held formal pharmacy qualifications. Among medical workers, 40% used antibiotics without prescriptions and 56% failed to complete treatment courses. Infections were more common in females (77%) than males (23%), with the highest prevalence in younger age groups (<32 years, 39.4%). Staphylococcus spp (32%) and E. coli (27%) were the most frequent isolates. Overall resistance was high (75%), particularly in Pseudomonas spp (100%), E. coli (83%), and Staphylococcus spp (76%). Azithromycin (67%) and Doxycycline (49%) showed the highest resistance rates, while Meropenem (2%) and Nalidixic acid (3%) remained largely effective. These findings highlight alarming levels of antibiotic resistance in Gharyan, driven by misuse and poor prescribing practices. Strengthening pharmacist and physician training, enforcing prescription regulations, and raising public awareness are essential to mitigate resistance and preserve antibiotic efficacy.